Globally optimal trial design and risk sharing arrangements are key to avoiding opportunity costs of delay and enabling equitable, feasible and effective global vaccine research and implementation in current or future pandemics - Eckermann, Simon (Frontiers in Public Health, 2022)
Global vaccination in the face of pandemics such as COVID-19 and new variants is a race against time. Avoiding the opportunity costs of delay and the associated health, social, and downstream economic impacts is a challenge and an imperative. Failures to address the global challenges posed by COVID-19 have become increasingly evident as waves of vaccine-evading mutations have emerged, facilitated by unequal vaccination coverage and diminishing immunity against new variants worldwide. To address these challenges, societal decision-makers (governments) and industry manufacturer interests must be better aligned for rapid, globally optimal trial design, ideally with research coverage, implementation, and accessibility of effective vaccines across joint research, implementation, and distribution cycles to address pandemic evolution in real time. Value of information (VoI) methods for optimal global trial design and risk-sharing arrangements align the research, distribution, and implementation interests and efforts globally to meet head-on the imperative of avoiding opportunity costs of delay and enabling consistent global solutions with maximizing local and global net benefits. They uniquely enable feasible early adoption of the most promising strategies in real time while the best globally translatable evidence is collected and interests are aligned for global distribution and implementation. Furthermore, these methods are generally shown to be imperative for feasible, fast, and optimal solutions across joint research, reimbursement, and regulatory processes for current and future pandemics and other global existential threats. Establishing pathways for globally optimal trial designs, risk-sharing agreements, and efficient translation to practice is urgent on many fronts.